Characterization of Activated carbons Prepared from a Locally Available Material by Iodine Number - Shrestha, Rajeshwar Man (Journal of the Institute of Engineering, 2018)
The adsorption of Iodine by the activated carbons prepared from a locally available material Lapsi Seed Stone has been studied. Various activated carbons were prepared by varying the parameters such as ratio of Lapsi Seed Stone particles to Phosphoric acid, percentage of phosphoric acid concentration, carbonization temperature and carbonization time. Determination of Iodine numbers of the activated carbons was done by the standard method. The effect of various preparation conditions on Iodine number of different activated carbons is also investigated. The optimum conditions for the preparation of activated carbon are found to be 400 ° C -the carbonization temperature, 4 hours - the carbonization time, 1:1- the ratio of Lapsi Seed Stone particles and Phosphoric acid and 50 %- the percentage of phosphoric acid concentration. Journal of the Institute of Engineering, 2017, 13(1): 139-144